The High Rate of Divorce Amid The Covid-19 Pandemic: An Legal Empiric Observation - Irahatmi Kaharu, Iyam Irahatmi; Muhdar, Gamar; Alizea Sybelle, Jan; Budiono, Arief (Fakultas Hukum Universitas Islam Malang, 2024)
Divorce happens due to continuous disputes and fights due to economic reasons. This research aims to analyze the factors causing the increasing rate of divorce as well as its main causes amid the pandemic in Ternate City. This paper employed the normative juridical method which is a literary study that studies documents. Results showed that divorce is the last resort. Economic status is the factor that wives often use to file for a divorce, as husbands are no longer able to provide for the wife, causing family conflicts that lead to divorce. The second factor is the rampant cases of work termination. This has become one of the main causes of divorce amid the Covid-19 pandemic.